1990
DOI: 10.1002/cncr.1990.66.s5.1074
|View full text |Cite
|
Sign up to set email alerts
|

A Controlled Trial of Castration With and Without Nilutamide in Metastatic Prostatic Carcinoma

Abstract: A randomized double‐blind trial in patients with disseminated, previously untreated prostate cancer (Stage D2) was conducted in eight Canadian centers. All 203 patients enrolled in this study underwent bilateral orchiectomy and were randomized to receive either the nonsteroidal anti‐androgen nilutamide or a placebo. Patient responses were graded according to the criteria of the National Prostatic Cancer Project (NPCP). Patients treated with nilutamide had a significantly greater number of positive objective re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

1992
1992
2003
2003

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…Three large controlled studies [13,18,19] support Labrie's hypothesis with a significant improvement in both time to disease progression and survival in the combination arm in comparison to the monotherapy treatment. However, two other studies comparing goserelin acetate alone and in combination with flutamide [15,20] and also a com bined analysis [21] of one of the studies previously cited [18] showed no difference in survival time.…”
Section: Resultsmentioning
confidence: 90%
“…Three large controlled studies [13,18,19] support Labrie's hypothesis with a significant improvement in both time to disease progression and survival in the combination arm in comparison to the monotherapy treatment. However, two other studies comparing goserelin acetate alone and in combination with flutamide [15,20] and also a com bined analysis [21] of one of the studies previously cited [18] showed no difference in survival time.…”
Section: Resultsmentioning
confidence: 90%
“…On reviewing the entire safety database for Casodex, only 1 patient (<0.1 %) has been withdrawn because of diarrhoea. The incidence of diarrhoea with flu tamide when used either as monotherapy or in combina tion with castration has, however, been reported as 2-5% Problems of light/dark adaptation and pulmonary fi brosis, both of which have been reported with nilutamide [13][14][15], have not been witnessed with Casodex.…”
Section: Resultsmentioning
confidence: 99%
“…Nilutamide has, however, a reported rate of alcohol intolerance of 19% [13,15]. for any reason, such as death, progression, adverse events) and 9% had died.…”
Section: Resultsmentioning
confidence: 99%
“…No statistically significant differences between the groups were found with respect to either time to progression (mean 21 and 18 months respectively) or survival (mean 31 and 30 months). Similarly, studies with nilutamide in combination with either orchidectomy or LH-RH analogue showed no statistically significant difference in time to progression and median survival from the castration alone treatment (medical or surgical; Brisset et al, 1987;Knönagel et al, 1989;Béland et al, 1990;Crawford et al, 1990;Le Duc et al, 1990;Namer et al, 1990). CPA has also been evaluated in combination therapy and there was no significant difference in survival between CPA plus goserelin acetate and the LH-RH analogue alone (Di Silverio et al, 1990;Brewster et al, 1992).…”
Section: Combined Androgen Blockade (Cab)mentioning
confidence: 99%